2015
DOI: 10.1002/ana.24535
|View full text |Cite
|
Sign up to set email alerts
|

TPM3 deletions cause a hypercontractile congenital muscle stiffness phenotype

Abstract: Objective Mutations in TPM3, encoding Tpm3.12, cause a clinically and histopathologically diverse group of myopathies characterized by muscle weakness. We report two patients with novel de novo Tpm3.12 single glutamic acid deletions at positions ΔE218 and ΔE224, resulting in a significant hypercontractile phenotype with congenital muscle stiffness, rather than weakness, and respiratory failure in one case. Methods The effect of the Tpm3.12 deletions on the contractile properties in dissected patient myofiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…However, within the NEM3 cohort, we observed marked variation in the Ca 2+ -sensitivity of force between patients, with lower than normal Ca 2+ -sensitivity in four patients (Fig.2H). A mutation/patient specific effect on Ca 2+ -sensitivity of force has previously been reported for myopathy associated mutations in ACTA1 25, 26 , TPM2 and TPM3 38, 51, 52 . When assessing the location of the mutated residues within the actin molecule we found that three of four mutations causing a decreased calcium sensitivity were located in subdomain 4 (see Fig.1 for details).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, within the NEM3 cohort, we observed marked variation in the Ca 2+ -sensitivity of force between patients, with lower than normal Ca 2+ -sensitivity in four patients (Fig.2H). A mutation/patient specific effect on Ca 2+ -sensitivity of force has previously been reported for myopathy associated mutations in ACTA1 25, 26 , TPM2 and TPM3 38, 51, 52 . When assessing the location of the mutated residues within the actin molecule we found that three of four mutations causing a decreased calcium sensitivity were located in subdomain 4 (see Fig.1 for details).…”
Section: Discussionmentioning
confidence: 75%
“…A mutation/patient-specific effect on Ca 21 sensitivity of force has previously been reported for myopathy-associated mutations in ACTA1, 25,26 TPM2, and TPM3. 38,51,52 When assessing the location of the mutated residues within the actin molecule, we found that 3 of 4 mutations causing a decreased calcium sensitivity were located in subdomain 4 (see Fig 1 for details). This cluster is not associated with a particular area of known function, and given the low number of mutations it is difficult to determine whether a true association between Ca 21 sensitivity and mutations in this domain exists.…”
Section: Is the Shift Toward A Higher Proportion Of Type 1 Fibers A Pmentioning
confidence: 99%
“…and D.H., unpublished observations). A search of the literature for mutations in additional sarcomeric proteins associated with myopathy and tremor revealed further cases of patients with mutations in genes encoding thick (MYH2 and MYL2) and thin (TNNT1, TPM3, and NEB) filament proteins (Supplementary Table 2), [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] suggesting that crossbridge dysregulation may emerge as a myogenic tremor generator beyond the MYBPC1 mutations reported here. Additional studies in transgenic animals to further elucidate the physiology of this novel type of tremor and get more insight into tremor-causing mechanisms are in preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the structure of troponin mobile regions will not only lead to understanding the changes that occur upon its regulation, but also to predicting the effect of a mutation or a pharmacological agent. For example, just by knowing the structure of tropomyosin and its exact interactions with actin it has been possible to predict the effect of disease-causing mutations (Marston et al, 2013; Donkervoort et al, 2015). With troponin it is not possible to make such predictions at the moment, as the structure is still unresolved.…”
Section: Discussionmentioning
confidence: 99%